HUBUNGAN TEBAL HUJAN DENGAN DEBIT ALIRAN RATA-RATA HARIAN DAN DEBIT PUNCAK HARIAN PADA DAERAH TANGKAPAN AIR AREAL BEKAS TEBANGAN DAN AREAL TEGAKAN BENIH DI PT. NARKATA RIMBA KALIMANTAN TIMUR - , DIAH PERMATA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Narkata Rimba is one holder of tropical natural forest concession in East Kalimantan which the forest status included into limited producting forest and located in watershed Telen hulu. In RKT 1 2012, PT. Narkata Rimba does the harvesting activity. According to Asdak (2010), harvesting activity where do in DAS hulu area, in a certain area, can give the influence to the flow discharge increasing in streams. In addition, rainfall in PT. Narkata Rimba is high, according to Schmidt dan Fergusson climate classification included into A climate type (very wet). So, itâs important to know relationship between highly rainfall towards harvesting impact in the form of flow discharge changing as a output from DAS system. This research aimed to determine the relationship between rainfall depth with daily average flow discharge and daily peak flow discharge on log over area and seed stand area. This research done in log over area and seed stand area catchment. The flow discharge data take with volumetric method in SPAS 2 . Rainfall depth data recorded with Automatic Rainfall Recorder (ARR). And then, flow discharge data and water stage data used to make discharge rating curve to change water stage from Automatic Water Level Recorder (AWLR) to flow discharge data. Daily average flow discharge data and daily peak flow discharge data obtained from Hydrograph analysis. Then, regression analyzed to know the relationship between rainfall depth with daily average flow discharge and daily peak flow discharge in Log Over Area Petak 1404 and Seed stand area. The results showed that there was positive influence between rainfall depth with daily average flow discharge and daily peak flow discharge in log over area and seed stand area. Daily average flow discharge in can be estimate with rainfall depth with formula Q = 0,131(P) + 1,796 with coefficients of determination (R 2 ) 0,875, whereas in seed stand area with formula Q = 0,106(P) + 1,316 with coefficients of determination (R 2 ) 0,835. Daily peak flow discharge in log over area can be estimate with rainfall depth with formula Q = 0,385(P) + 3,288 with coefficients of determination (R 2 ) 0,901, whereas in seed stand area with formula Q = 0,9(P) + 1,455 with coefficients of determination (R 2 ) 0,915